Composition of Small Mammals between Disturbed and Undisturbed Areas of Peat Swamp Forest in Ayer Hitam Utara Forest Reserve in Johor - Sim, Sin Rou; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2025)
Ayer Hitam Utara Forest Reserve (AHUFR) is the largest remaining peat swamp forest in Johor. Studies on small mammals are still limited given lots of research being done in AHUFR. This study aimed to make a checklist of small mammals and compare their composition between disturbed and undisturbed areas of AHUFR for a total of 12 sampling days. Sampling involved 24 cage traps and 4 mist nets across two sampling sites in each disturbed and undisturbed areas. Four species were recorded: Tupaia glis (Common Treeshrew), Leopoldamys sabanus (Long-tailed Giant Rat), Maxomys rajah (Rajah Spiny Rat), and Rhinolophus trifoliatus (Trefoil Horseshoe Bat). While both areas recorded three species, the undisturbed area had a higher abundance (11 individuals) compared to the disturbed area (seven individuals). The disturbed area exhibited a higher Shannon-Weiner index (H’ = 0.9557) and evenness (E = 0.8699) and a T-test (T-test = 0.674; p-value > 0.05) indicated no statistically significant difference between the areas. The findings can provide baseline data for future research and conservation efforts.